Kesesuaian Uji Imunokromatografi dengan Enzyme Linked Fluorescent Assay untuk Deteksi Hepatitis B Surface Antigen - Nomira Putri; Dianni Arma Wahyu Setia Ningsih; Bella Lucintarillova Arif Lubis (Journal of Mandalika Literature, 2024)
Hepatitis B virus (VHB) infection is a global health problem. Hepatitis B surface antigen (HBsAg) as a serologic marker of hepaitis B virus infection can be detected by immunochromatography and Enzyme Linked Fluorescent Assay (ELFA). The aim of this study is to prove the agreement of immunochromatographic test with ELFA to detect HBsAg. This study used a cross-sectional analytic method on 30 patients for HBsAg examination at the Central Laboratory of Clinical Pathology. HBsAg was tested in patient's serum using immunochromatography and ELFA test. The agreement between the two methods was analyzed using the Kappa test. The Kappa coefficient between the two tests was 0.69 with good strength. The concordance of immunochromatographic assay with ELFA to detect HBsAg in this study gave good results.. : infeksi virus hepatitis b (VHB) merupakan maslah kesehatan global. Hepatitis B surface antigen (HBsAg) sebagai penanda serologi infeksi virus hepaitis B dapat dideteksi dengan uji imunokromatografi dan Enzyme Linked Fluorescent Assay (ELFA). Penelitian ini bertujuan untuk membuktikan kesesuaian uji imunokromatografi dengan ELFA untuk mendeteksi HBsAg. Penelitian ini menggunakan metode analitik potong lintang terhadap 30 pasien untuk pemeriksaan HBsAg di Laboratorium Sentral Patologi Klinik. Pemeriksaan HBsAg terhadap serum pasien menggunakan uji imunokromatografi dan ELFA. Kesesuaian antara kedua metode dianalisis menggunakan uji Kappa. Koefisien Kappa antara kedua pemeriksaan ini adalah 0,69 dengan kekuatan yang baik. Kesesuaian uji imunokromatografi dengan ELFA untuk mendeteksi HBsAg pada penelitian ini memberikan hasil yang baik.